Development and validation of a dual language needs assessment tool for people living with colorectal cancer (NeAT-CC) - Nur Nadiatul Asyikin Bujang; Yek Ching Kong; Muthukkumaran Thiagarajan; April Camilla Roslani; Muhammad Radzi Abu Hassan; Matin Mellor Abdullah; Mehesinder Singh; Wan Zamaniah Wan Ishak; Awang Bulgiba; Mahmoud Danaee; Nirmala Bhoo-Pathy (PLoS ONE, 2025)
Background Needs assessment tools may guide optimization of clinical services to be more patient-centered. As needs of patients living with and beyond colorectal cancer (CRC) may also be influenced by socio-cultural backgrounds and healthcare ecosystems, we developed and validated a needs assessment questionnaire for CRC in a multi-ethnic, low-and middle-income setting. Methods The study methodology was guided by the COSMIN checklist. Items generation was based on findings from independent qualitative inquiries with patients, input from cancer stakeholders, and literature review. Following translation into Malay language, content and face validation were undertaken. The tool was administered to 300 individuals living with and beyond CRC. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were performed. Criterion validity was assessed using EORTC QLQ-C30 and QLQ-CR29 questionnaires. Results The 48-item bilingual needs assessment tool for colorectal cancer (NeAT-CC) encompassed six domains of needs, namely (i) diagnosis, (ii) psychosocial and information, (iii) healthcare, (iv) practical and living with cancer, (v) financial and (vi) employment. Cronbach’s alpha was above 0.70 for all domains, indicating good internal consistency. CFA also demonstrated acceptable convergent and divergent validity with composite reliability >0.70 and Heterotrait–Monotrait index <0.90 for all constructs. Criterion validity was established given the significant correlation with quality of life. The NeAT-CC was easily understandable, took 15–20 minutes for completion and may be self-administered. Conclusions Utilization of NeAT-CC may facilitate optimization of supportive and survivorship care services following CRC in local settings. The tool has wider potential for adaptation in other multi-ethnic and/or low and middle-income settings.